2017
DOI: 10.1152/jn.00615.2016
|View full text |Cite
|
Sign up to set email alerts
|

Human primary somatosensory cortex is differentially involved in vibrotaction and nociception

Abstract: The role of the primary somatosensory cortex (S1) in vibrotaction is well established. In contrast, its involvement in nociception is still debated. Here we test whether S1 is similarly involved in the processing of nonnociceptive and nociceptive somatosensory input in humans by comparing the aftereffects of high-definition transcranial direct current stimulation (HD-tDCS) of S1 on the event-related potentials (ERPs) elicited by nonnociceptive and nociceptive somatosensory stimuli delivered to the ipsilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 94 publications
1
27
0
Order By: Relevance
“…The fact that the N1 wave of CEPs exhibits a clear phase reversal over central areas suggests a strong contribution of a tangential source close to the central sulcus. In fact, this scalp topography closely resembles the scalp topography of the early-latency responses of somatosensory-evoked potentials, such as the N20 wave elicited by stimulation of the median nerve (Lenoir et al, 2017; Allison et al, 1991). These scalp topographies are compatible with activity originating from the posterior bank of the central sulcus, i.e.…”
Section: Discussionmentioning
confidence: 70%
“…The fact that the N1 wave of CEPs exhibits a clear phase reversal over central areas suggests a strong contribution of a tangential source close to the central sulcus. In fact, this scalp topography closely resembles the scalp topography of the early-latency responses of somatosensory-evoked potentials, such as the N20 wave elicited by stimulation of the median nerve (Lenoir et al, 2017; Allison et al, 1991). These scalp topographies are compatible with activity originating from the posterior bank of the central sulcus, i.e.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies have shown that tDCS over the somatosensory cortices can affect SEPs (Matsunaga et al, 2004 ; Dieckhofer et al, 2006 ; Sugawara et al, 2015 ; Lenoir et al, 2017 ; Nakagawa et al, 2017 ), tactile discrimination of vibratory stimuli (Rogalewski et al, 2004 ) and spatial acuity (Ragert et al, 2008 ; Fujimoto et al, 2014 , 2016 ; Hilgenstock et al, 2016 ). Taken together with previous findings, the current results support the efficacy of tDCS for affecting somatosensory function.…”
Section: Discussionmentioning
confidence: 99%
“…cortical) is to measure the latency to elicit a cortical evoked potential following noxious stimulus. For electrical stimulation, the latency of the somatosensory evoked potential following the stimulation of median nerve is ~20 ms for Caucasians and the onset is ~18 ms (Cruccu et al, 2008;Lenoir et al, 2017) and reduction in corticospinal excitability prior to this latency likely comes from the spinal level. This reduction in corticospinal excitability is possible because noxious electrical stimulus bypasses the cutaneous receptors and depolarizes not only Aδ and C nociceptive fibres with a slow conduction velocity, but also the non-nociceptive Aβ-fibres, which are larger and have a lower threshold and a faster velocity of conduction (Algoet et al, 2018;Beall et al, 1977;Mouraux et al, 2010).…”
Section: Phasic Painmentioning
confidence: 99%